Generalized equation for the design of a baffle to generate arbitrary flow velocity profiles. Issue 149 (February 2016) - Choi, M.K.; Cho, M.K.; Lee, H.W.; Jung, H.; Lee, J.W.
Abstract: Flow velocity profiles can be transformed using non-uniform resistance elements, and the design equation for the distribution of pores in a single baffle plate of uniform thickness was formulated to transform any flow velocity profile into another arbitrary velocity profile. The proposed equation was validated first through numerical analysis for a couple of velocity profiles with satisfactory results, and then verified by an experiment with an excellent agreement of maximum difference less than 4.3%. Also found was an empirical relation between the number of holes in the baffle and the accuracy of the transformed velocity profile.